Legal Protection For Notaries By The Notary Honorary Council as A Witness in The Case Of Identity Forgery By The Parties Making The Deed - Khairani; Argi Putra Finalo; Trie Rahmi Gettari (Ekasakti Journal of Law and Justice, 2024)
Notary is a legal profession whose rights and obligations have been regulated in such a way in Law Number 30 of 2004 concerning the Notary Position (hereinafter referred to as UUJN). Where in Article 1 of the UUJN states "Notary is a public official who is authorized to make authentic deeds and other authorities as referred to in this Law". However, in terms of carrying out his professional duties, it is not uncommon for a notary to stumble into legal cases such as being a witness in an authentic deed dispute that he has made due to identity forgery by the parties who made the deed. Therefore, the existence of a Notary as a witness in a court hearing requires legal protection, especially from the Notary Honorary Assembly. Departing from this problem, this study has two problem formulations, First:  What is the Role of the Notary Honorary Assembly towards Notaries as Witnesses in the Case of Identity Forgery by the Parties Making the Deed?, Second: What is the Legal Protection for Notaries as Witnesses in the Case of Identity Forgery by the Parties Making the Deed?. So to answer these problems, this study uses a juridical-normative research method. The results of this study state that the UUJN has given birth to one of the legal protection instruments for notaries, namely the Notary Honorary Assembly Institution, where one of the main tasks is to give approval or rejection of the request for approval to summon notaries to attend investigations, prosecutions and judicial processes. However, in practice this is still often ignored so that there are many notaries who are harmed by a criminal case.